Perancangan Sistem Informasi Booking Berbasis Web (Studi Kasus : Sah Project Wedding Organizer) - Ayu Latifah Deti; Khaerul Ma’mur (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
SAH Project Wedding Organizer is a service that provides wedding packages starting from wedding planning, make up, decorations to party tools. The problem with SAH Project Wedding Organizer is that customers still have to come to the office or chat by whatsapp to admin to book WO services. Therefore, with a web-based system for ordering WO services. In making this wedding organizer information system used the PHP programming language, MySQL database software, and the framework CodeIgniter. And also using the Protoype method as an approach to the analysis and design of information systems and using UML as a tool to implement the process of analysis and design of information systems. With this web system, customers who want to book can directly open the SAH Project Wedding Organizer web and can choose a wedding package and the required date. In accordance with the conclusion of the questionnaire results in this web have a percentage result of 88.33%.